Development of a tool to characterize business models for forestry services - Benjaminsson, Filip (2018)
The Northern Periphery and Arctic (NPA) region is a part of northern Europe with common characteristics of low population density and low economic diversity, but with an abundance of natural resources. The region covers areas in eight countries, of which this study has focused on Sweden, Finland, Great Britain, and Ireland. Forests constitute a main resource in the region, with potential to create job opportu-nities. In Sweden and Finland, forestry service contractors have struggled with low profitability. Studies show reasons such as insufficient turnover, and shortcomings in business relationships and operational conditions. There are also identified differ-ences in contractors’ business structures. No studies have however targeted their business model design, which has been shown to provide competitive advantages in other industries. Therefore, this study aimed to adapt, validate and evaluate a business model canvas (BMC) for characterization of forestry service businesses by a three-step approach: 1) Adaptation: Experts in applying BMCs and in forestry services were interviewed targeting suitable adaptations to forestry. 2) Validation: The ability of the adapted canvas to capture variations between contractors and markets was tested by interviewing experts in the focus countries. 3) Evaluation: Outcomes were evaluated to adjust and propose a For-estry BMC (FBMC). Results revealed many similarities and differences, both within and between markets. Commonly, customer companies have a strong influence on business model design. Key differences were found in details of business model components, which moti-vates the need for a structured tool such as the FBMC to ensure covering of all rele-vant aspects. I norra Europas utkant finns glest befolkade områden med låg ekonomisk diversitet men stora naturresurser. Skogsresurserna har stor potential att skapa arbetstillfällen och driva på glesbygdsutvecklingen. Europeiska Unionen (EU) har identifierat om-råden som uppfyller dessa och några ytterligare kriterier och ...